Phosphorus Fractions of Biochar-Amended Plinthalqualf under Clean and Waste Water Irrigation Regimes in Northern Ghana - Obodai, M.S. (University Of Ghana, 2018)
The reactive nature of phosphorus leads to the formation of insoluble Fe, Al and Ca bound phosphate compounds in highly weathered tropical soils, thus limiting P availability for plant uptake. Biochar with its heterogeneous surface properties can influence phosphorus dynamics in tropical soils. To examine phosphorus fractions in a biochar-amended Plinthaqualf, samples were taken from low yielding soils in northern Ghana that had three cycles of vegetable production under clean and waste water irrigation regimes for two seasons. Sampling was done from irrigated soils amended with (i) biochar (B) at application rate of 20 tonnes per hectare, (ii) inorganic fertilizer (Ammonium sulphate-(NH₄)₂SO₄) according to normal agricultural practice (IF-NAP), (iii) a combination of biochar (B) plus (NH₄)₂SO₄) and a control (soil) inclusive. Phosphorus fractionation of the control soil and soil amended plots (B, (NH₄)₂SO₄, and B + (NH₄)₂SO₄) was assessed by a modified Hedley’s method. Water was used as an initial extractant before the resin was applied to ascertain the amount of water leachable P in the soils. The interaction of the amendments [biochar (B), (NH₄)₂SO₄ and (B + (NH₄)₂SO₄)] was assessed, and it showed an increase in the most labile Pi or available Pi (H2O-P, + Resin-P + NaHCO3-P) as well as moderately labile P (NaOH-Pi) fractions in the soils, thus, making P more available for plant uptake. There were significant correlations (p < 0.05; p < 0.01) among P fractions expressing a continuum among the P fractions, The P fractions were also related to the chemical properties of the soil and amended soils. The study showed that the water leachable P highly correlated (p< 0.01) with soil organic carbon, available P and total P at probabilities of 0.43, 0.42 and 0.70, respectively and forms about 24% on the average of total available P fraction of the soil. The study also showed that waste water irrigation regime gave a marginal P increment compared to the clean water irrigation, especially in the biochar treatment plots. Inference from the results of the study showed that all three amendments; biochar (B), (NH₄)₂SO₄ and (B + (NH₄)₂SO₄) significantly (p < 0.005) improved soil fertility parameters especially, P availability. However, B+(NH₄)₂SO₄ performed much better in the release of most labile P and that it could be used to improve the bioavailability of P in acidic soils such as those used in the study. High amount of water leachable P implies a possible loss of about a fourth of the soil available P if irrigation was done beyond field capacity or water saturation point of the soil. It is therefore, recommended that drip or sprinkle irrigation at reduced amounts is adopted to possibly forestall about a quarter (24%) of the available P that could be lost through the current mode of irrigation. It is also recommended that fortified biochar (B+(NH₄)₂SO₄) should be applied to improve P status of highly weathered soils (e.g. Plinthaqualfs) of northern Ghana. Further studies on application of P sources B, (NH₄)₂SO₄ and B+(NH₄)₂SO₄ should be conducted at different rates to ascertain optimum P application. In addition, the high correlations between water leachable P and the total P and also the available P could be exploited to bypass the use of expensive chemicals through modelling of a mathematical relation.
MPhil.
Keywords: Phosphorus Fraction; Biochar-Amended Plinthalqualf; Water Irrigation; Northern Ghana